Magnetic Resonance-Guided Stereotactic Body Radiotherapy of Liver Tumors: Initial Clinical Experience and Patient-Reported Outcomes - Weykamp, Fabian; Hoegen, Philipp; Klüter, Sebastian; Spindeldreier, C. Katharina; König, Laila; Seidensaal, Katharina; Regnery, Sebastian; Liermann, Jakob; Rippke, Carolin; Koerber, Stefan A.; Buchele, Carolin; Debus, Jürgen; et al. (Frontiers in Oncology, 2021)
Purpose/Objective Stereotactic body radiation therapy (SBRT) has emerged as a valid treatment alternative for non-resectable liver metastases or hepatocellular carcinomas (HCC). Magnetic resonance (MR) guided SBRT has a high potential of further improving treatment quality, allowing for higher, tumoricidal irradiation doses whilst simultaneously sparing organs at risk. However, data on treatment outcome and especially patient acceptance is still scarce. Material/Methods We performed a subgroup analysis of an ongoing prospective observational study comprising patients with liver metastases or HCC. Patients were treated with ablative MR-guided SBRT at the MRIdian Linac in the Department of Radiation Oncology at Heidelberg University Hospital between January 2019 and February 2020. Local control (LC) and overall survival (OS) analysis was performed using the Kaplan-Meier method. An in-house designed patient-reported outcome questionnaire was used to measure patients’ experience with the MR-Linac treatment. Toxicity was evaluated using the Common Terminology Criteria for Adverse Events (CTCAE v. 5.0). Results Twenty patients (with n=18 metastases; n=2 HCC) received MR-guided SBRT for in total 26 malign liver lesions. Median biologically effective dose (BED at α/β=10) was 105.0Gy (range: 67.2-112.5Gy) and median planning target volume was 57.20mL (range: 17.4-445.0mL). Median treatment time was 39.0min (range: 26.0-67.0min). At 1-year, LC was 88.1% and OS was 84.0%. Gastrointestinal toxicity grade I° occurred in 30.0% and grade II° in 5.0% of the patients with no grade III° or higher toxicity. Overall treatment experience was rated positively, with items scoring MR-Linac staff’s performance and items concerning the breath hold process being among the top positively rated elements. Worst scored items were treatment duration, positioning and low temperature. Conclusion MR-guided SBRT of liver tumors is a well-tolerated and well-accepted treatment modality. Initial results are promising with excellent local control and only mildest toxicity. However, prospective studies are warranted to truly assess the potential of MR-guided liver SBRT and to identify which patients profit most from this new versatile technology.